2017
DOI: 10.1016/j.jaci.2016.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Life-threatening NLRC4-associated hyperinflammation successfully treated with IL-18 inhibition

Abstract: Capsule Summary NLRC4-inflammasome hyperactivity causes infantile-onset Macrophage Activation Syndrome and enterocolitis with extraordinary serum IL-18 elevation (NLRC4-MAS). Herein, we report a critically ill infant with severe, refractory NLRC4-MAS who showed sustained response to treatment with experimental IL-18 inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
235
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 303 publications
(251 citation statements)
references
References 10 publications
(24 reference statements)
2
235
0
2
Order By: Relevance
“…This supports the idea that mutated CARD8 T60 exerts a dominant-negative activity also results in secretion of IL-18 and, while this cytokine may reduce inflammation by contributing to epithelial integrity as mentioned above, it also may have proinflammatory properties of it own. This is seen in patients with NLRC4 abnormalities that do not respond to IL-1β blockade, but do respond to a combination of agents that block both IL-β and IL-18 (35). The occurrence of a CD phenotype in the proband and his relatives bearing the CARD8 mutation and manifesting increased NLRP3 activity, but not in CAPS patients who bear NLRP3 mutations that also cause increased NLRP3 activity, raises questions about the genetic and/or environmental factors necessary for disease appearance.…”
Section: Discussionmentioning
confidence: 99%
“…This supports the idea that mutated CARD8 T60 exerts a dominant-negative activity also results in secretion of IL-18 and, while this cytokine may reduce inflammation by contributing to epithelial integrity as mentioned above, it also may have proinflammatory properties of it own. This is seen in patients with NLRC4 abnormalities that do not respond to IL-1β blockade, but do respond to a combination of agents that block both IL-β and IL-18 (35). The occurrence of a CD phenotype in the proband and his relatives bearing the CARD8 mutation and manifesting increased NLRP3 activity, but not in CAPS patients who bear NLRP3 mutations that also cause increased NLRP3 activity, raises questions about the genetic and/or environmental factors necessary for disease appearance.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the pathogenesis of sepsis has not been fully elucidated, and studies in China and other countries have confirmed the correlation between sepsis and the general inflammatory network. Interleukin-18 (IL-18) is a pleiotropic proinflammatory cytokine11 with abnormal expression in sepsis,12 suggesting its potential use as a prognostic indicator of sepsis. Nevertheless, sepsis is frequently complicated by organ failure or dysfunction to varying degrees, where the heart is the most susceptible organ 13.…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal biopsies/autopsy specimens from all reported AIFEC patients consistently show a mixed inflammatory infiltrate, villous flattening with tissue edema, epithelial erosions and tissue autolysis (2,3,30,35). Activated macrophages have been visualized in some (31) but not all AIFEC intestinal tissue samples (2,3,30), raising the possibility that mutant NLRC4 in IECs, not myeloid cells, is the primary driver of gut pathology. Due to feeding intolerance, many AIFEC patients temporarily require parenteral nutrition, including the oldest known AIFEC patient, now 46 years old.…”
Section: Aifecmentioning
confidence: 95%
“…AIFEC flares have been appropriately compared to MAS; both entities share signature IL-1β symptomology (fever, tachycardia) and interferon gamma (IFNγ)-related histopathology (hemophagocytosis). Peripheral blood transcriptional profiles generated from two AIFEC patients in flare suggest MAS-like myeloid cell activation and cytotoxic T-cell dysfunction (2,30). In its most extreme form, an AIFEC flare can be confused with primary hemophagocytic lymphohistiocytosis (HLH), with hypertriglyeridemia, coagulopathy, multi-lineage cytopenias, elevated soluble IL-2 receptor and poor in vitro cytotoxicity (2,3,30,31,32).…”
Section: Aifecmentioning
confidence: 99%